The mediator role of the psychological contract in light of the linking between training needs and organizational commitment - exploratory search - الملا, عبد الرحمن مصطفى (Journal of Economics and Administrative Sciences, 2018)
The purpose of this research shed light on the analysis of the relationship between training needs and organizational commitment and the role of a variable contract psychological, and start search of a dilemma thought provoking fundamental questions revolve around the search was the answer to all those questions of tricks theoretical framework to the variables of research first and test models of the relationship and impact secondly During six hypotheses major, The objective of the research the impact of the factors that affect training needs in organizational commitment center the psychological contract, and applied research on a sample of 100 individuals working in the engineering department and maintenance at the Department of Medical City, has been relying on the resolution as an essential tool for the collection of data and information the existence of a correlation between training needs and organizational commitment, also appeared that there is a significant effect of training needs in organizational commitment, and the level of influence increases with the level of contract psychological analyzed using a number of statistical methods, and research found to a number of conclusions delusional existence correlation moral between training needs and organizational commitment, also appeared that there is a significant effect of training needs in organizational commitment, and the level of influence increases with the level of contract psychological, has included research four axes went first to the methodology and the second for framing theory and the third to view and analyze the results and test hypotheses, while allocated fourth of the conclusions and recommendations